Correlação entre cefalometria e antropometria para determinação do tipo facial - Ramires, Rossana Ribeiro (2008)
Introduction: human face with its bony and muscular structures has singular and peculiar characteristics. It may be classified in three types, associated with the variation of shape and craniofacial configuration, both in vertical and horizontal planes, directly affecting dental occlusion, face harmony, orofacial musculature and oral functions. Aim: to correlate cephalometric with anthropometric and facial analysis findings on determining the facial type. Method: 105 leukoderm adults were involved, 34 male and 71 female aging between 20 and 40 years old. Data were collected in December 2006 in an orthodontic clinic located at Belo Horizonte. Cephalometric findings to determinate facial types were compared to seven anthropometric facial measurements, three anthropometric facial proportions and three anthropometric facial indices, in addition to facial type identification through clinical facial analysis of photographs. Results: for the male, there were significant statistical differences in facial types classified by cephalometry among the average values of some anthropometric variables: anterior face height, lower face height, middle face height, inferior face height, facial index, lower facial index, upper facial index and mandibular proportion. For the female, there were significant statistical differences with: anterior face height, lower face height, middle face height, inferior face height, ramus height and mandibular proportion. The classification of facial type based on facial analysis did not satisfactorily match with the cephalometric classification. Conclusion: anthropometric indices and proportions provided reliable data to determine long face, in men; long and short face, in women. Facial type classification based only on facial analysis was not considered trustworthy when used separately